Експериментальне проектування як етап у формуванні основоположних засад архітектури промислових будівель - Житкова, Наталія Юріївна; Zhitkova Natalia (КНУБА, 2020)
У статті досліджено особливий зв'язок промислового підприємства та урбаністичного середовища, врахування певних особливостей розміщення підприємства в містобудівному середовищі, а також відповідні чинники архітектурно-будівельних схем модернізації виробництва для розуміння сучасного процесу реконструкції та реновації промислових об’єктів в історичному контексті. The topic of the article examines the special connection between an industrial enterprise and the urbanistic environment, taking into account certain features of the location of an enterprise in an urban planning environment, as well as the corresponding factors of the architectural and construction scheme of modernization of production to understand the modern process of reconstruction and renovation of industrial facilities in a historical context. In search of figurative plastic stylistic expressiveness, architects in the 1920s and 1940s drew attention to engineering structures, machines and units were placed outside, which already at that time became a visual carrier of iconic-shaped symbols of the aesthetics of industrial culture. Subsequently, during the period of new experimentation in the 60s and 70s, the volumes of the engineering infrastructure were included in the structure of the volumetric-spatial solution of the production environment as an element of compositional construction based on block-modules given by the technology. The revival of the modern synthesis of arts is talentedly embodied in the metallurgical enterprise "Interpipe": frescoes, volumetric compositions of the modern Danish artist - Olafur Eliasson have formed a modern industrial enterprise where almost classical heritage of the experimental period of the 60s-early 70s remained the basis and prolific area.
Экспериментальное проектирование как этап в формировании основополагающих принципов архитектуры промышленных зданий
Experimental design as a stage in the formation of the fundamental principles of the architecture of industrial buildings.
Keywords: експериментальне будівництво; індустріалізація; реконструкція; архітектура промислового підприємства; experimental construction; industrialization; reconstruction; architecture of an industrial enterprise